Milestones in the Historical Development of Early Childhood Education in India - Shahab, Falak; Babu M, Sameer (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
Early Childhood Development (ECD) is a sensitive phase in human growth that determines a child's future learning, behaviour, and health. This paper analyses the importance of ECD, especially in the Indian context, focusing on historical developments, key milestones, current frameworks, challenges in implementation, and ongoing efforts to improve ECD services. The findings underscore that investment in quality ECD must be made so that more children, particularly those from less privileged backgrounds, have opportunities to access the same. Last, there is a discussion on who plays what role in shaping effective ECD practices, such as government initiatives and NGOs.